KAJIAN FIQH MUAMALAH TERHADAP KONSEP PENGELOLAAN DANA BAGI HASIL DI PERBANKAN SYARIAH - Usammah Usammah (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2017)
In the syariah bank system, customer funds are managed in the form of deposit or investment. The manner of deposit and investment is clearly different from the deposits in conventional banks, where deposits are an attempt to lend money. The concept of deposit fund means whenever the customer needs it then the sharia bank must be able to fulfill it. While the concept of investment is a business that bear the risk, it means that every opportunity to gain profit from the business undertaken, in which there is also the risk to accept losses, then between customers and banks share both the benefits and risks. The profit-sharing system makes the size of the profit received by customers following the size of the profits of Islamic banks. The greater the profit of sharia banks the more profit nasbahnya. Unlike conventional banks, the bank's profit is not shared with its customers. No matter how much the bank profits, then the customer is paid only a percentage of the funds he saved only.